ANALISIS PANDANGAN MASYARAKAT TERHADAP PESANTREN TEBUIRENG 3 - Muhammad Taufiqurrohman; Darma Putra; Samsu Samsu; Marzuki Darusman; Cahaya Purnama; Nia Nursaktila (LPPM Universitas Islam Ibrahimy Banyuwangi, 2025)
This study examines the community's views on the existence of Tebuireng 3 Islamic Boarding School, with a focus on perceptions of teachers, educational programs, and students' contributions to community service. The main objective of this study is to understand how the Petalongan Village community interacts and perceives Tebuireng 3 Islamic Boarding School in social, religious, and educational contexts. This study uses a qualitative method with a phenomenological approach, data obtained through in-depth interviews and participatory observation with informants selected by purposive sampling. The results of this study indicate that the Petalongan Village community views Tebuireng 3 Islamic Boarding School positively, especially in terms of student discipline, teaching quality, and active role in religious activities in the community. The flagship program of memorizing the Qur'an and the involvement of students in socio-religious activities also strengthen the image of Tebuireng 3 Islamic Boarding School as an institution that contributes to the formation of the spiritual character of the younger generation. This study concludes that the existence of Tebuireng 3 Islamic Boarding School is not only as an Islamic educational institution, but also as a vehicle for social transformation that is able to establish harmonious relations with the community.